Cutaneous metastasis of colon adenocarcinoma - Kemal, Yasemin (Turk J Surg, 2018)
Skin metastasis originating from colorectal cancer is a rare entity and usually signifies poor prognosis. We present a case of a 62-year-old male patient who presented with a cutaneous metastatic focus on his forehead after five years of the primary treatment of colon cancer. Complete response from the cutaneous metastasis nodule was achieved with radiotherapy. The patient is still alive and under a second-line palliative chemotherapy regimen because of the multiple liver metastases. It is important for physicians to be aware of skin metastasis in patients with an oncology history.